Analytical and philosophical issues of studying current problems in the development of modern derivatology - Shepel, Yuri; Pidmohylna, Nataliia; Amichba, Dimona; Shkurko, Olena; Muliar, Iryna (Linguistics and Culture Review, 2021)
The relevance of the research undertaken is determined by the insufficient description of the cognitive approach in relation to word formation units, the unjustifiably rare use of word formation data by the conceptology that is actively developing in linguistics, and the need to form semantic-cognitive analysis procedures relevant to the research object to determine the boundaries of complex units of the word-formation level. The article focuses on the philosophical issues of linguistics, in particular word formation. The peculiarity of linguistics at the end of the 20th century, the essence of which is the recognition of the cognitive conditioning of the main linguistic units and structures, is noted. It is noted that the materialization of certain concepts with the help of linguistic means always consists of a certain ordering, systematization, distribution by headings, categorization. The main function of the analysis and classification of derived words is determined not as groups of derived words or a system of derivational types, but the principles of construction and deployment of complex derivational fragments (blocks, rows, fields), taking into account derivational units larger than a word, analytical analogs of derived words, constructions in the derivation function, only way to represent the derivative and its semantics.